2011
DOI: 10.1590/s0104-11692011000700013
|View full text |Cite
|
Sign up to set email alerts
|

Relações entre contexto familiar e uso de drogas em adolescentes de ensino médio

Abstract: Este estudo teve por objetivo descrever características do contexto familiar de adolescentes de ensino secundário e suas relações com o uso de substâncias psicoativas. Utilizou-se desenho de estudo descritivo transversal, do tipo survey, com amostra de 657 estudantes de ensino secundário da cidade de Leon, Nicarágua, correspondendo a 31% do universo investigado. As informações foram coletadas por meio de questionário autoadministrado e anônimo. Os resultados mostraram que 56% dos adolescentes conviviam com amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 9 publications
0
9
0
17
Order By: Relevance
“…Corroborating what has been said above, Garcia et al (2011), analyzing the relationship between substance abuse and nuclear family structure, found that a higher quantity of drug users in the study were from homes with a traditional nuclear family structure: father, mother and children, which contradicts the common belief that non-traditional family arrangements can lead to drug use. The above mentioned study also identified that, in families of psychoactive substance users, there was often violence, or drug use by other family members, suggesting that substance abuse is linked with conflict in family relationships rather than the construction of the family.…”
Section: Introductionmentioning
confidence: 42%
“…Corroborating what has been said above, Garcia et al (2011), analyzing the relationship between substance abuse and nuclear family structure, found that a higher quantity of drug users in the study were from homes with a traditional nuclear family structure: father, mother and children, which contradicts the common belief that non-traditional family arrangements can lead to drug use. The above mentioned study also identified that, in families of psychoactive substance users, there was often violence, or drug use by other family members, suggesting that substance abuse is linked with conflict in family relationships rather than the construction of the family.…”
Section: Introductionmentioning
confidence: 42%
“…O principal mérito do artigo é a demonstração de que no contexto do uso de crack, como para outras drogas 6,24,25 , as famílias não se situam apenas no polo de proteção, mas podem contribuir para a iniciação, para a manutenção ou para o retorno ao consumo de drogas 11,[26][27][28][29][30] . Manifestações dos entrevistados detalham exemplos de situações assim, como na referência a uma recaída promovida, pelo menos em parte, pelo uso que o irmão seguia fazendo, invadindo espaços do entrevistado e mantendo o comportamento de consumo como uma opção, no dia a dia naquele domicílio.…”
Section: Discussionunclassified
“…Na Nicarágua, jovens usuários de drogas ilícitas que procediam de famílias identificadas como disfuncionais pelos autores diziam-se rechaçados e percebiam menos apoio ou cuidados pouco efetivos e apoio insuficiente na direção da mudança de comportamentos 25 . A postura de pais e mães na relação cotidiana com seus filhos também aparece como vetor desse ambiente.…”
Section: Discussionunclassified
“…There is also an increase in the number of accidents at work and traffic, deaths and a fall in the productivity of men and women of different ethnic groups or levels of education, decreasing the quality of life [4,5]. When reflecting on family and society, these consequences make drug abuse a global public health problem [6].…”
Section: Introductionmentioning
confidence: 99%